8 Assessment of consistency in quantification of ribonucleic acid across multiple methods. (28th November 2020) - DeCarlo, Andrea N; Parrish, Joseph; Bridges, William; Pratt, Scott
Abstract: Quantification and assessment of quality of ribonucleic acid (RNA) is essential for assays determining gene expression including qRT-PCR, northern blotting, and RNA sequencing. Methods assessing RNA abundance and quality vary in detection range and specificity, in part due to their differences in how quantification is achieved. Agilent chip technology utilizes fluorescent labeling of nucleic acids coupled to electrophoresis to separate RNA based on size. Nanodrop utilizes spectrophotometry assesses quantity nucleic acids based on absorption of light and allows for an estimation of purity using the A260/280 (nucleic acid to protein) ratio. RiboGreen assays utilize a fluorescent intercalating dye that specifically targets single-stranded RNA. The objective of this study was to determine the most accurate method of RNA quantification between these three assays. Male pituitary samples (n = 220) were collected at a local abattoir, anterior lobe isolated, flash frozen in methanol dry-ice bath, and stored at -80°C until further processing. Total RNA was isolated from all samples and samples were subjected to spectrophotometry, Agilent nano chip assay, and Ribogreen assay. Data were analyzed for differences in standard deviation of total yield (mg/g) across all methods and each pair of methods using an O'Brien test for unequal variances. Standard deviation differed due to quantification method (P = 0.0002). Over 5 times greater variability in quantification was observed between Agilent chip technology compared to nanodrop (P = 0.0036), 2 times greater between nanodrop and Ribogreen (P < 0.0001), and 10 times greater variation between Agilent and Ribogreen methods (P = 0.0029). The Ribogreen assay provides the smallest variation in quantification from sample to sample and is the most reliable method out of the three technologies for quantification of RNA; however, it does not address issues of RNA quality.